Legal analysis of Jordanian medical negligence with reference to civil law system - Hajjat, Wadah Y.A (Ahmand Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
This research focuses on issues of medical negligence and laws governing the relationship between the physician and patient. It sheds light on the mechanisms of implementing the law relating to the medical negligence through an analysis of the liability of the physician in Islamic law and civil law systems, bearing in mind that Jordanian legislation does not specifically cater for issues relating to the medical liability, resulting in the absence of a clear method to secure the right of the patient-victim .The study attests to the similarity between the rules of Islamic law and those of most modern legal systems. This goes on to emphasise the fact that Islamic law is ever relevant to any place and period. Furthermore, the research contains a detailed exposition of the legal nature of civil liability affecting physicians as grounded in contractual and negligence liability, their pillars, as well as divergent opinions regarding their adaptation. Reference is made to the principles developed by the judicial system of Egypt, France and Jordan including the views of jurists as adopted by the courts. The research analyses the elements of medical liability, highlighting the position of the Jordanian legislation which differs from other systems in the protection of the interest of the patient. General rule that the obligation of the physician is to make competent efforts, while the obligation to achieve the result is an exception. In the end, one has to admit that it is difficult to come to a definite conclusion on the issue of civil liability of the physician. This is in view of the sensitivity and the unique features of the human body. The contribution of the research is reflected in the suggestions and recommendations which will provide a firm basis to address legal problems and challenges facing lawyers and judges owing to the flaws inherent in the Jordanian legislation. This humble research is expected to enrich the Jordanian law library on medical negligence.